Prevalence and associated factors of prolonged grief disorder in Chinese parents bereaved by losing their only child. (February 2020) - Zhou, Ningning; Wen, Jun; Stelzer, Eva-Maria; Killikelly, Clare; Yu, Wei; Xu, Xin; Shi, Guangyuan; Luo, Haoxian; Wang, Jianping; Maercker, Andreas
Highlights: Over one third of Chinese shidu parents suffered from prolonged grief disorder according to the ICD-11 guidelines. The prevalence of prolonged grief disorder of the ICD-11 guidelines was almost twice as that of Prigerson et al. (2009) criteria. Younger age, being female, living in a rural area, low monthly income, shorter time since loss and comorbid chronic physical diseases correlated with severer grief symptoms. Abstract: In China, parents who have lost their only child and remained childless are labelled Shidu (失独) parents. Previous research suggests high levels of psychological distress in this population, yet little is known regarding the prevalence of prolonged grief disorder (PGD) based on the new ICD-11 formulation. The present study examined prevalence rates and associated factors of prolonged grief disorder in this population. 1030 Chinese Shidu parents (381 male, 643 female) who were recruited through convenient sampling completed questionnaires assessing grief severity. Multiple linear regression models were used to examine socio-demographic, loss-related and self-reported number of chronic physical conditions associated with PGD symptoms. Results showed prevalence rate was 35.5% based on the ICD-11 PGD criteria, which was almost twice as that of Prigerson et al. (2009) criteria. Younger age of parents, being a mother, living in a rural place, lower monthly income per capital, shorter time since loss and more comorbid chronic physical conditions were related to severer PGD symptoms. The present findings revealed high rates of PGD experienced by Chinese Shidu parents and identified key risk factors which can be used for future prevention or intervention designs in this population.